EFFECTIVENESS OF CNC TURNING AND CNC MILLING IN MACHINING PROCESS - Rahmatullah Rahmatullah; Arfis Amiruddin; Sudirman Lubis (CERED Indonesia Institute, 2021)
Technological developments and advances in the digital era are currently growing rapidly along with the times, so that they have an impact in all sectors including the manufacturing industry sector. Competition in the manufacturing industry is getting higher, both in the field of supporting equipment technology and in the production sector. This makes all interested parties and companies compete to create more technical and practical equipment. The manufacture of equipment, parts, components and manufactured products in the past still used conventional machines such as lathes, milling machines, scrap machines and other machines in general and are still used today for certain jobs. The manufacture of parts such as shafts, factory components, heavy equipment components, car components, aircraft components and other engineering equipment components still uses conventional machines in a small part of the manufacture of parts and components. In jobs that require high production rates, short production times and high and uniform quality, using conventional machines is not recommended. Machines with CNC technology with computer-assisted numerical control or the like have been the solution for decades. In this paper, we will discuss the effectiveness of CNC machines, especially the TU-3A EMCO CNC milling as an illustration by developing G, M code programming, and product examples.